Antimicrobial activity of red pigments derived from Monascus purpureus: A comparison to industrial red pigments. Issue 1 (28th October 2021) - Gökmen, Gökhan Gurur; Şılbır, Mehmet Selim; Göksungur, Yekta; Kışla, Duygu
Abstract: Background: In recent years, the various advantages of fungal pigments over other natural or synthetic pigments have opened new avenues for wide range of applications in different industries. This study aims to determine the antimicrobial activity of fungal pigment produced by Monascus purpureus CMU001, against some Gr(+) and Gr(−) bacteria, yeasts and molds. Method: In this study, the 96‐well microplate dilution and macro dilution methods were used to determine the minimum inhibitory concentration (MIC) values of pigments on tested microorganisms. Therefore, the microbial plating method was performed to observe the antifungal activity of pigment since the MIC values could not be determined on molds. Results: The antibacterial activity of Monascus pigment against all tested bacteria was higher than the commercial red pigment. The minimum bactericidal concentration on Bacillus cereus ATCC11778 was determined as 256 mg/ml for the commercial pigment and 128 mg/ml for Monascus pigment. The MIC values could not be determined for both pigments against yeast and molds even at the highest possible concentration. Conclusion: The Monascus pigments have a big potential to use in different industries such as foods, textile, and biomedical products, since the high inhibitory effects was confirmed on various food‐borne and pathogenic bacteria and fungi. Although the specific mechanism and properties of the antimicrobial activity of Monascus pigments are still unknown, the differences between lab‐produced and commercial pigments showed that the antimicrobial activity was based on the type of microorganism, growth conditions, and the composition of culture medium.